When reporting Nocardia spp is not enough. Brain abscess caused by Nocardia farcinica. Issue 2 (20th February 2020) - Zintgraff, J.; Prieto, M.; Peña, M.; Simoiz, F.; Rosenblit, S.; D'Alessandro, D.; Garces, A. Fernandez; Di Matteo, V.; Astesana, R.; Panno, M.
Abstract : Abscesses caused by the genus Nocardia spp are relatively rare, accounting for approximately 2 % of all brain abscesses, but with a significantly higher mortality. Special stains of brain abscess material from a 60-year-old man showed Gram-positive branching bacilli and the presence of long, acid-fast branching filamentous bacilli suggesting Nocardia infection. Presented here is a case of multidisciplinary management of a patient who developed cerebral abscesses by Nocardia farcinica, confirmed by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), that was susceptible to trimethoprim/sulfamethoxazole, linezolid, imipenem and not susceptible to minocycline. This case highlights the importance of performing subtyping and antimicrobial testing in order to improve clinical and treatment outcomes due to patterns of antibiotics resistance among Nocardia species.